The Role of Social Media Among Women Survivors of Sexual Violence - Pasha, Sartika Sari Wardanhi Dh; Furqan, Rahmatul; Hidayatullah, Fauzan (Universitas Mercu Buana, 2025)
Addressing sexual violence against women is an urgent global concern that demands action at all societal levels. Unlike other forms of violence against women, sexual violence is particularly challenging to expose and address due to its association with societal norms of morality. The emergence of social media as a pivotal platform has enabled survivors to share their experiences, fostering potential preventive measures for others. Through digital platforms, survivors can promote awareness, solidarity, and collective strength, driving societal and structural changes. This research focuses on two primary objectives: 1) How to optimize social media to establish a protective environment for women survivors of sexual violence? 2) What role does the interplay of social media communication play in facilitating the empowerment of these women survivors? A qualitative descriptive approach with a case study methodology will be employed, utilizing snowball sampling for informants selection to address these aims effectively. The study aims to offer insights into how social media serves as a tool for survivors seeking support, validation, and advocacy. It will provide recommendations for using social media in prevention and education campaigns against sexual violence, aiming to enhance support for women survivors and advocate for more inclusive societal changes. Through this research, we seek to contribute to a deeper understanding of the intersection between social media and sexual violence survivorship, highlighting the platform's role in fostering empowerment and societal transformation.